2015
DOI: 10.1002/asia.201501238
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Potencies of PtII‐ and PdII‐linked M2L4 Coordination Capsules with Improved Selectivity

Abstract: Pt(II) - and Pd(II)-linked M2 L4 coordination capsules, providing a confined cavity encircled by polyaromatic frameworks, exhibit anticancer activities superior to cisplatin against two types of leukemic cells (HL-60 and SKW-3) and pronounced toxicity against cisplatin-resistant cells (HL-60/CDDP). Notably, the cytotoxic selectivities of the Pt(II) and Pd(II) capsules toward cancerous cells are up to 5.3-fold higher than that of cisplatin, as estimated through the non-malignant/malignant-cells toxicity ratio e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 57 publications
(17 reference statements)
0
44
1
Order By: Relevance
“…Additionally, they have measured the cytotoxicity of mixtures of the cages and cisplatin and unsurprisingly have found that those mixtures are more cytotoxic than cage alone (IC 50 = 2–13 μM). Yoshizawa, Ahmedova and co-workers have also found that [M 2 ( L ) 4 ] 4+ (M = Pd 2+ or Pt 2+ ) cages with similar, but more hydrophobic, dipyridyl anthracenyl ligands ( L anthracene ) display high anticancer activity (IC 50 values range from 0.9 to 37.4 μM against HL-60, HL-60/Dox, HT-29, T-24, SKW-3 cancer cell lines) (Ahmedova et al, 2016 ; Anife et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they have measured the cytotoxicity of mixtures of the cages and cisplatin and unsurprisingly have found that those mixtures are more cytotoxic than cage alone (IC 50 = 2–13 μM). Yoshizawa, Ahmedova and co-workers have also found that [M 2 ( L ) 4 ] 4+ (M = Pd 2+ or Pt 2+ ) cages with similar, but more hydrophobic, dipyridyl anthracenyl ligands ( L anthracene ) display high anticancer activity (IC 50 values range from 0.9 to 37.4 μM against HL-60, HL-60/Dox, HT-29, T-24, SKW-3 cancer cell lines) (Ahmedova et al, 2016 ; Anife et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 For instance, cages have been explored in the context of "artificial enzyme" catalysis, 3 for hazardous chemical capture, 4 reactive intermediate stabilisation, 2c for drug delivery and release, 5 as well as in molecular sensing 6 and in biology. 7 More recently, desirable photophysical properties such as emission tuning, 8 encapsulation-assisted energy and electron transfer, 9 longlived charge-separated state lifetimes 10 and photoresponsive guest uptake/release 11 have been achieved by integrating emissive moieties such as metalloporphyrins, metal complexes or fluorescent ligands, into the backbone of metallosupramolecular macrocycles and cages. 6a, 12 Ruthenium(II) polypyridyl complexes can generally access multiple oxidation states, and they enjoy a rich history in photocatalysis.…”
mentioning
confidence: 99%
“…[1][2][3] Despite the extraordinary growth of the chemistry of SCCs,s tudies reporting on their potential biomedical applications are so far extremely limited. [7][8][9][10] Pt-ensembles can in principle be designed to mimic complex cellular regulatory motifs.Therefore,they can act through unusual modes of action potentially capable to overcome the drawbacks (for example resistance) of clinically applied Pt II drugs. [2,[4][5][6] We and others focused our efforts on the intrinsic anticancer potential of SCCs, [5] devoting particular attention to those supramolecules where platinum drives the self-assembly.…”
Section: Introductionmentioning
confidence: 99%